Numerical Study of Heat Transfer Characteristics in High Pressure Steam Turbine During Stop Unit Process with Sliding Pressure - Budi Santoso; Bambang Arip Dwiyantoro (The International Journal of Mechanical Engineering and Sciences, 2022)
During maintenance of the turbine and its auxiliary equipment, which requires a stop of the turbine oil system equipment and an open turbine casing, the first stage metal temperature requirement must be below 150°C. The normal stop unit method with natural cooling takes about 14 to 17 days. In order to speed up the cooling time to 5 days, a forced cooling turbine is needed using the stop unit method with sliding pressure. The heat transfer that occurs in the high-pressure turbine during the stop unit process with sliding pressure was investigated using the numerical method of CFD simulation. The 2D geometry design was made from high-pressure turbine cutouts images. Then meshing was made. The solver stage and the post-processing stage were set. The simulation was running in a steady state and followed by transients. The validation method was to compare the first stage metal temperature parameter between the actual process and the results of the CFD simulation at a load of 350 MW, then re-simulate it at 500 MW and 645 MW. The stop unit process with sliding pressure starting at 645MW resulted in the best final cooling compared to the stop unit at 500 MW and 350MW loads. By increasing the main steam flow, the resulting cooling increases. By increasing the value of the fluid flow velocity, the Reynolds number increases, so the convection heat coefficient also increases.